2016
DOI: 10.1186/s11689-016-9178-1
|View full text |Cite
|
Sign up to set email alerts
|

Postural orientation and equilibrium processes associated with increased postural sway in autism spectrum disorder (ASD)

Abstract: BackgroundIncreased postural sway has been repeatedly documented in children with autism spectrum disorder (ASD). Characterizing the control processes underlying this deficit, including postural orientation and equilibrium, may provide key insights into neurophysiological mechanisms associated with ASD. Postural orientation refers to children’s ability to actively align their trunk and head with respect to their base of support, while postural equilibrium is an active process whereby children coordinate ankle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 46 publications
(80 reference statements)
6
44
0
3
Order By: Relevance
“…Studies of postural control in ASD have implicated sensory feedback processes. Individuals with ASD are less stable than typically developing (TD) controls during standing [1,2,[16][17][18], and they show more severe postural control deficits, including increased postural sway, when sensory feedback information is occluded or removed [1,3,17,19]. These findings suggest that individuals with ASD may place greater demands than controls on feedback processes in order to maintain stability.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies of postural control in ASD have implicated sensory feedback processes. Individuals with ASD are less stable than typically developing (TD) controls during standing [1,2,[16][17][18], and they show more severe postural control deficits, including increased postural sway, when sensory feedback information is occluded or removed [1,3,17,19]. These findings suggest that individuals with ASD may place greater demands than controls on feedback processes in order to maintain stability.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with ASD also show more severe postural control deficits during dynamic postures. For example, Wang et al (2016) found that individuals with ASD demonstrated increased center of pressure (COP) variability during a dynamic stance condition in which they intentionally swayed along the mediolateral (ML) or anteroposterior (AP) axis. Elevations in COP variability in ASD were more severe during the dynamic compared to a static standing condition, suggesting that individuals with ASD show greater levels of impairment during conditions in which demands on feedback motor control processes are increased [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ankle angle for the 8-minute trial was segmented into sixteen 30s time windows and Standard Deviation (SD) was calculated in each window. SD has been previously used in studies assessing postural control in ASD (Wang et al, 2016). Spectral properties of the ankle angle waveforms in the first (a1) and last (a6) windows of adaptation were also calculated.…”
Section: Methodsmentioning
confidence: 99%